Counterfeit products containing medical active ingredients İlaç etkin maddesi İçeren sahte ürünler - GÜLHAN, REZZAN (My University, 2013)
Objective: Counterfeit and illegal drug trafficking is a worldwide problem. The most important substances of this trade include phosphodiesterase 5 enzyme inhibitors (PD5EI) which are used for the treatment of penil erection dysfunction, and weight loss products. These products are generally manufactured at clandestine laboratories and marketed under inappropriate conditions. The aim of this study was to examine these types of products, which have been seized by the judicial authorities in Turkey and to draw attention on the subject. Material and Methods: Products, non-alcoholic beverages and pharmaceutical compounds in the form of capsule, tablet or cream containing unlabeled sibutramine, PD5EI, and also products which were sold with these compounds seized by legal authorities and sent to the Council of Forensic Medicine for analysis between July-December 2011 were examined in this study. Results: The analysis of seized products revealed that 9 (69.2%) pharmaceutical compounds contained sildenafil, 3 (23.1%) contained local anesthetics, 1 (7.7%) contained sibutramine and beverages contained thiosildenafil. All of the products were counterfeit and they did not have a licence of production from legal authorities in Turkey or other countries, or import permission on their packages. Conclusion: Especially, PD5Is or weight loss products containing sibutramine which are widely marketed all over the world are also sold by illegal ways in our country, and because of inappropriate manufacturing and transport conditions, they cause a serious threat to public health. © 2013 by Türkiye Klinikleri.

Amaç: Dünyada sahte ve kaçak ilaç ticareti illegal yollarla oldukça yaygın olarak yapılmaktadır. Bu ticaretin en önemli elemanları penil ereksiyon disfonksiyon bozukluğu tedavisinde kullanılan fosfodiesteraz tip 5 enzim inhibitörleri (FD5Eİ) ve zayıflama ürünleridir. Bu ürünler genellikle merdiven-altı laboratuvarlarda imal edilmekte ve uygunsuz koşullarda ambalajlanarak kullanıcıya ulaştırılmaktadırlar. Bu çalışmadaki amacımız Türkiye'de adli makamlarca ele geçirilmiş olan bu tür ürünleri incelemek ve konuya dikkat çekebilmektir. Gereç ve Yöntemler: Adli mercilerce ele geçirilerek Temmuz-Aralık 2011 tarihleri arasında Adli Tıp Kurumu'na incelenmek üzere gönderilen kapsül, tablet, krem gibi farmasötik formlar ve alkolsüz içecek olarak ele geçirilen ürünler arasında muhteviyatında FD5Eİ veya sibutramin tespit edilen ya da bu muhteviyattaki maddelerle birlikte satılırken yakalanan ürünler çalışmaya dâhil edilmiştir. Bulgular: On üç farmasötik preparatın 9’unda (%69,2) sildenafil, 3’ünde (%23,1) lokal anestezik madde, 1’inde (%7,7) sibutramin, 1 içecek maddesinde ise tiyosildenafil bulunmuştur. Ürünlerin tamamının sahte ürünler olduğu, ambalajları üzerinde Türkiye veya başka bir ülkeye ait Bakanlık ruhsatı, üretim ya da ithal izninin bulunmadığı belirlenmiştir. Sonuç: Tüm dünyada yaygın şekilde pazarlanan özellikle FD5Eİ ya da sibutramin gibi ürünler, ülkemizde de kaçak yollarla satılmakta olup, eksik ve yanlış içerik bilgisi, uygun olmayan imalat ve nakliye koşulları nedeniyle halk sağlığı açısından ciddi tehdit oluşturmaktadır.
Counterfeit products containing medical active ingredients
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Counterfeit drugs; Drug toxicity; Phosphodiesterase 5 inhibitors; Sibutramine; Sildenafil; Sahte ilaçlar; sildenafil; sibutramin; ilaç toksisitesi; fosfodiesteraz 5 inhibitörleri; Counterfeit drugs; sibutramine; drug toxicity; phosphodiesterase 5 inhibitors